Hedonic modelling of housing markets using geographical information system and spatial statistics: Glasgow, Scotland - Ismail, Suriatini; MacGregor, Bryan (2006)
This paper presents the results of a simultaneous consideration of detailed accessibility measures and spatial autocorrelation in house price hedonic modelling. It illustrates the application of GIS and spatial statistics in the estimation of hedonic models for the entire housing market in Glasgow, Scotland, using 2,715 house prices for 2002 and 61 independent variables. GIS is used in this study to construct spatial variables including detailed accessibility measures, to help detect spatial autocorrelation, and for map visualisation. Spatial statistics are used to test formally and model explicitly the spatial autocorrelation. The results suggest that an individual accessibility measure is more influential than a zonal accessibility measure because the former is able to capture the micro effect of location on house price. Furthermore, the application of spatial statistics can produce more accurate and reliable estimates of implicit prices.